Significance of the cribriform pattern in predicting the prognosis of lung adenocarcinoma patients: A systematic review and meta-analysis - Jun Peng; Xianquan Zhang; Yan Huang; Changhui Liu; Shuyang Li; Jinfeng Liu (PLoS ONE, 2025)
Background A number of studies have shown that various histological subtypes of lung adenocarcinoma have different clinical prognoses, but the cribriform pattern, as a unique histological subtype, plays an important role in the prognosis of patients with lung adenocarcinoma. Objective In this meta-analysis, we evaluated the role of the cribriform pattern in the overall survival of patients with lung adenocarcinoma, which may provide valuable information for the treatment of patients with lung adenocarcinoma. This also provides an important basis for dividing the cribriform pattern into a new histological subtype and classifying it. Methods We searched the literature from the PubMed, Embase, Cochrane and Web of Science online databases; extracted the data and characteristics of each study; and extracted and calculated hazard ratios (HRs) with 95% confidence intervals (CIs) to evaluate the impact of the cribriform pattern on the prognosis of patients with lung adenocarcinoma. Results A total of 10 articles were included in the study according to the preset criteria, with a total of 5487 research subjects. The hazard ratio for the relationship between the cribriform pattern and the overall survival rate of patients with lung adenocarcinoma was 2.05 (95% CI: 1.76–2.39). The prognosis of patients with positive spread through air spaces in the cribriform pattern was significantly worse than that of patients with negative spread through air spaces in the cribriform pattern, with a hazard ratio of 2.58 (95% CI: 1.84–3.62). There was a significant difference in prognosis between patients with the cribriform pattern and those with low-grade and intermediate-grade lung adenocarcinoma, but there was no significant difference in prognosis between patients with the cribriform pattern and those with high-grade lung adenocarcinoma, with hazard ratios of 2.12 (95% CI: 1.12–4.00), 7.70 (95% CI: 2.15–36.20) and 0.96 (95% CI: 0.54–2.40), respectively. Therefore, the cribriform pattern should be used as a histological subtype of high-grade tumors, thus influencing the postoperative prognosis of patients with lung adenocarcinoma. Conclusion The presence of the cribriform pattern is an independent risk factor for postoperative overall survival in patients with lung adenocarcinoma. The cribriform pattern should be considered a new histological subtype of lung adenocarcinoma and classified with solid carcinoma and micropapillary adenocarcinoma as high-grade tumors.